Cultural And Citizenship Literacy In Elementary School: Systematic Literature Review And Bibliometric Analysis - Sindiawati, Mita Putri; Darmayanti, Mela; Nurfaridah, Elisa; Nurjanah, Siti (International Conference on Elementary Education, 2025)
Cultural and civic literacy is important to be taught in Elementary Schools so that students are able to accept, adapt and act wisely to face diversity and challenges in the 21st century. This study aims to analyze cultural and civic literacy in Elementary School through a qualitative approach with a systematic literature review. The research procedure uses the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method with the help of the Publish or Perish application for article data collection, and VOSviewer for bibliometric analysis. The results showed an increasing trend of publications related to cultural and civic literacy every year. The implementation of this literacy is done through five methods: the use of learning media, teaching materials, habituation, integration in learning, and school programs. There are supporting and inhibiting factors for the implementation of cultural and civic literacy in Elementary Schools. Subjects that often integrate cultural and civic literacy are Social Science, Civic Education and Cultural Arts. The results of this study are expected to enrich the educational literature and provide insights into effective educational practices in developing cultural and civic literacy among primary school students.